"Fraudonomics": Cartooning against Structural Adjustment in Togo. (April 2021) - Frisch, Robin
Abstract: This article offers a sensitive reading of oppositional political cartoons in Togo in the early 1990s, during the period of structural adjustment, which was accompanied by the swift reversal of democratizing trends and the restoration of authoritarian rule. Togolese satirists perceived this moment as a moment of "fraudonomics", thus contesting rampant corruption and clientelism in politics. They poked fun at the president, local politicians, businesspeople, and bureaucrats of the international institutions. The article begins by examining the making of satirical newspapers with a focus on the biographies of the satirists. As students, they started out on the adventure of publication with their own money and learned most of their drawing and printing techniques as work progressed. Secondly, an analysis of the readership shows that, although the satirical newspapers were a crucial element of the media in the early 1990s, it was mostly an elitist and urban phenomenon. The third section analyses the changing visual repertoire of contention through in-depth analysis of four selected caricatures.